Use of likelihood ratios improves interpretation of laboratory testing for pulmonary sarcoidosis - De Smet, Dieter; Martens, Geert A; Berghe, Bram Vanden; Meysman, Marc; Heylen, Olivier; Gorus, Frans K; De Waele, Marc (American journal of clinical pathology, 2010)
Laboratory tests for pulmonary sarcoidosis (percentage lymphocytes and CD4/CD8 ratio in bronchoalveolar lavage fluid and serum angiotensin-converting enzyme activity) lack sensitivity and specificity. In a retrospective study of 153 subjects under suspicion of pulmonary sarcoidosis (36 cases and 117 patients with other diseases [control patients]), we defined likelihood ratios (LRs) for rationally selected result intervals of these tests, which improve clinical interpretation as compared with dichotomous interpretation based on a single cutoff value. By using logistic regression analysis, we further integrated the 3 individual tests into a unified algorithm that could rule out diagnosis in 57 (48.7%) of the 177 control subjects and confirm diagnosis in 12 (33%) of the 36 pulmonary sarcoidosis cases. We conclude that use of LRs improves interpretation of laboratory tests for pulmonary sarcoidosis. In addition, we present a prediction algorithm based on the combination of laboratory tests that helps clinicians confirm or exclude diagnosis in almost half of the study population.